Nutrients Mediate Intestinal Bacteria–Mucosal Immune Crosstalk - Ma, Ning; Guo, Pingting; Zhang, Jie; He, Ting; Kim, Sung Woo; Zhang, Guolong; Ma, Xi (Frontiers in Immunology, 2018)
The intestine is the shared site of nutrient digestion, microbiota colonization and immune cell location and this geographic proximity contributes to a large extent to their interaction. The onset and development of a great many diseases such as IBD and metabolic syndrome will be caused due to the imbalance of body immune. As a competent assistant, the intestinal bacteria is also critical in disease prevention and control. Moreover, the gut commensal bacteria are essential for development and normal operation of immune system and the pathogens are also closely bound up with physiological disorders and diseases mediated by immune imbalance. Understanding how our diet and nutrient affect bacterial composition and dynamic function, and the innate and adaptive status of our immune system, represents not only a research need but also an opportunity or challenge of improving health. Herein, this review focuses on the recent discoveries about intestinal bacteria-immune crosstalk and nutritional regulation on their interplay. With an aim to provide novel insights that will aid understanding their interactions.